Great Cause—Small Effect: Undeclared Genetically Engineered Orange Petunias Harbor an Inefficient Dihydroflavonol 4-Reductase - Haselmair-Gosch, Christian; Miosic, Silvija; Nitarska, Daria; Roth, Barbara L.; Walliser, Benjamin; Paltram, Renate; Lucaciu, Rares C.; Eidenberger, Lukas; Rattei, Thomas; Olbricht, Klaus; Stich, Karl; Halbwirth, Heidi (Frontiers in Plant Science, 2018)
A recall campaign for commercial, orange flowering petunia varieties in spring 2017 caused economic losses worldwide. The orange varieties were identified as undeclared genetically engineered (GE)-plants, harbouring a maize dihydroflavonol 4-reductase (DFR, A1), which was used in former scientific transgenic breeding attempts to enable formation of orange pelargonidin derivatives from the precursor dihydrokaempferol (DHK) in petunia. How and when the A1 cDNA entered the commercial breeding process is unclear. We provide an in-depth analysis of three orange petunia varieties, released by breeders from three countries, with respect to their transgenic construct, transcriptomes, anthocyanin composition, and flavonoid metabolism at the level of selected enzymes and genes. The two possible sources of the A1 cDNA in the undeclared GE-petunia can be discriminated by PCR. A special version of the A1 gene, the A1 type 2 allele, is present, which includes, at the 3’-end, an additional 144 bp segment from the non-viral transposable Cin4-1 sequence, which does not add any functional advantage with respect to DFR activity. This unequivocally points at the first scientific GE-petunia from the 1980s as the A1 source, which is further underpinned e.g. by the presence of specific restriction sites, parts of the untranslated sequences, and the same arrangement of the building blocks of the transformation plasmid used. Surprisingly, however, the GE-petunia cannot be distinguished from native red and blue varieties by their ability to convert DHK in common in vitro enzyme assays, as DHK is an inadequate substrate for both the petunia and maize DFR. Recombinant maize DFR underpins the low DHK acceptance, and, thus, the strikingly limited suitability of the A1 protein for a transgenic approach for breeding pelargonidin-based flower colour. The effect of single amino acid mutations on the substrate specificity of DFRs is demonstrated. Expression of the A1 gene is generally lower than the petunia DFR expression despite being under the control of the strong, constitutive p35S promoter. We show that a rare constellation in flavonoid metabolism - absence or strongly reduced activity of both flavonol synthase and B-ring hydroxylating enzymes - allows pelargonidin formation in the presence of DFRs with poor DHK acceptance.